Boosting Emerging Technology Adoption in SMEs: A Case Study of the Fashion Industry - Arianne Muthia Zahra; Wawan Dhewanto; Akbar Adhi Utama (Politeknik Negeri Bandung, 2021)
Small and medium enterprises (SMEs) provide a significant contribution to the economy and are amongst the target of governments’ digital transformation programs. Yet, existing advanced technology adoption models are based upon and targeted for large-scale companies and might not be applicable to the majority of firms in this segment. To address this issue, this study aims to explore ways in boosting the adoption of technologies relevant to SMEs by employing a qualitative research approach through in-depth interviews and focus group discussions with manufacturing SMEs in the fashion industry. Evidence of this study points to several main findings: (1) Leader's competencies, technology literacy, growth mindset, and supportive SME conditions provide positive sentiments towards emerging technologies. However, (2) SMEs must also consider the compatibilities of the technology and evaluate its advantage to the firms prior to adoption. Lastly, (3) stakeholders support and competitors influence are also shown to affect SME leaders, the SME, and the technology itself in terms of supporting technology adoption. This research contributes to the literature by uncovering current condition and needs of SMEs for their technological transformation. For relevant stakeholders, targets of transformation might be achieved if the particular concerns of SMEs have been addressed.